Strategic management of information, defense and sustainability policies in the context of legal Amazonia: The Sipam Case - ZUIN, Aparecida Luzia Alzira; Santos, Jean Carlo Silva dos (International Journal for Innovation Education and Research, 2019)
The object of this paper is to study the correlations existent between the strategic use of information and the articulation and implementation of defense policies, national security and sustainable development in Legal Amazonia. For such, it presents the Amazonia Protection System (SIPAM in the Portuguese acronym), verifying how these systems have contributed to the definition and implantation of those policies. For Amazonia, with its natural resources, threats and vulnerabilities, the perspectives of integration, security and national defense and sustainable development present huge challenges to be surmounted. For such, the efficient use of technology is a basic reference that should be included in public strategies and policies in those areas, which increasingly reflect the ways of life in the region's cities. In that context, SIPAM sits in a line of approach in which the guarantee of national sovereignty in Amazonia, besides the strategic-military enterprise, also includes the attention to local people's development, within an educational and integrating proposition. As a way of conclusion, we have found that SIPAM creates a paradigmatic model for local public management, in which organizations work with a shared set of information, as well as in an integrated way.